Assessment of American College of Rheumatology–Endorsed Quality Indicators in Rheumatoid Arthritis Patients: A Quality Improvement Initiative. Issue 2 (March 2016) - Anderson, Erik; Bajaj, Puneet; Raghavan, Siddharth; Patnaik, Asha; Roppelt, Heidi
Abstract : Background: The American College of Rheumatology endorses 7 rheumatoid arthritis (RA) quality indicators (QIs), which we used to access quality of care at our institution. Objective: The aim of this study was to assess the quality of care provided to RA patients at our outpatient rheumatology practice based on adherence to 7 QIs. Methods: We performed a retrospective paper chart review and included 356 RA patients to determine adherence to each QI. A χ 2 test analyzed trends in the assessment of disease activity and functional status. Results: There was excellent adherence to disease-modifying antirheumatic drug therapy (99.4%) and managing worsening disease (100%). Assessment of disease activity and functional status increased over the study period (72.8% to 94.2% and 70.8% to 93.4%, respectively). Despite this, none of our patients had disease prognosis classified and documented. Tuberculosis screening was done in 87.9%. Only a small percentage (1.4%) of patients met criteria for a glucocorticoid management plan, thus limiting our assessment of this QI. Conclusions: Excellent adherence to disease-modifying antirheumatic drug therapy and management is likely due to targeting clinical remission. Assessment of disease activity and functional status not only rose each year, but also is higher compared with similar studies. This may be due to an increased awareness of QIs and the utility of objective measures of disease activity. Deficient documentation of prognosis may be due to a lack of awareness of its importance. Suboptimal tuberculosis screening may be an artifact of poor documentation. We propose interventions to improve adherence.